2016
DOI: 10.1158/1535-7163.mct-15-0815
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomic Changes following PI3K Inhibition as Pharmacodynamic Biomarkers: Preclinical Discovery to Phase I Trial Evaluation

Abstract: PI3K plays a key role in cellular metabolism and cancer. Using a mass spectrometry-based metabolomics platform, we discovered that plasma concentrations of 26 metabolites, including amino acids, acylcarnitines, and phosphatidylcholines, were decreased in mice bearing PTEN-deficient tumors compared with non-tumor-bearing controls and in addition were increased following dosing with class I PI3K inhibitor pictilisib (GDC-0941). These candidate metabolomics biomarkers were evaluated in a phase I dose-escalation c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…A study showed that plasma levels of acetylcarnitine negatively correlated with tumor grade in patients with hepatocellular carcinoma 24 . Studies on plasma metabolites indicate that changes in the MAPK or PI3K pathways are associated with alterations in metabolites including amino acids, acylcarnitines, and phosphatidylcholines 25,26 . Therefore, we assumed that GCTs, often associated with mutations in either MAPK or PI3K pathways, exhibited decreased levels of acetylcarnitine and butyrlcarnitine.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that plasma levels of acetylcarnitine negatively correlated with tumor grade in patients with hepatocellular carcinoma 24 . Studies on plasma metabolites indicate that changes in the MAPK or PI3K pathways are associated with alterations in metabolites including amino acids, acylcarnitines, and phosphatidylcholines 25,26 . Therefore, we assumed that GCTs, often associated with mutations in either MAPK or PI3K pathways, exhibited decreased levels of acetylcarnitine and butyrlcarnitine.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Metabolomic studies of the same inhibitor show that plasma metabolites can be useful dose-dependent biomarkers of the response to therapy. 20 …”
Section: Discussionmentioning
confidence: 99%
“…It provides insight into normal physiology and pathomechanisms, and tools to characterise phenotypes. In the context of drug discovery and development, metabolites provide accessible biomarkers (Ang et al 2017(Ang et al , 2016Griffiths et al 2010).This is particularly important where the availability of human tumour biopsies is limited and the use of surrogate tissues, e.g. plasma, is essential to assess target engagement.…”
Section: Introductionmentioning
confidence: 99%
“…50 Page 2 of 11 mediated effects, assessment of the compound non-tumour related effects has the potential to (i) identify biomarkers, (ii) gain better understanding of the mechanism of action and (iii) predict potential side effects earlier in the drug development process before the clinical phases. We have previously demonstrated that metabolomic signatures established in preclinical studies can be used clinically as biomarkers of target engagement and/or predictors of tumour and compound specific responses (Ang et al 2017(Ang et al , 2016. In these studies, a workflow to generate tumour specific and target related metabolomic signatures was successfully applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation